Development of Coagulation Factor XII Antibodies for Inhibiting Vascular Device-Related Thrombosis - Kohs, T. C. L. (Cell Mol Bioeng, 2020)
INTRODUCTION: Vascular devices such as stents, hemodialyzers, and membrane oxygenators can activate blood coagulation and often require the use of systemic anticoagulants to selectively prevent intravascular thrombotic/embolic events or extracorporeal device failure. Coagulation factor (F)XII of the contact activation system has been shown to play an important role in initiating vascular device surface-initiated thrombus formation. As FXII is dispensable for hemostasis, targeting the contact activation system holds promise as a significantly safer strategy than traditional antithrombotics for preventing vascular device-associated thrombosis. OBJECTIVE: Generate and characterize anti-FXII monoclonal antibodies that inhibit FXII activation or activity. METHODS: Monoclonal antibodies against FXII were generated in FXII-deficient mice and evaluated for their binding and anticoagulant properties in purified and plasma systems, in whole blood flow-based assays, and in an in vivo non-human primate model of vascular device-initiated thrombus formation. RESULTS: A FXII antibody screen identified over 400 candidates, which were evaluated in binding studies and clotting assays. One non-inhibitor and six inhibitor antibodies were selected for characterization in functional assays. The most potent inhibitory antibody, 1B2, was found to prolong clotting times, inhibit fibrin generation on collagen under shear, and inhibit platelet deposition and fibrin formation in an extracorporeal membrane oxygenator deployed in a non-human primate. CONCLUSION: Selective contact activation inhibitors hold potential as useful tools for research applications as well as safe and effective inhibitors of vascular device-related thrombosis.